Olfactory impairment in Italian patients with chronic rhinosinusitis with nasal polyps: a patient-centered survey - Anastasi, Francesca; Canevari, Frank Rikki Mauritz; Gallo, Stefania; Gramellini, Giulia; Heffler, Enrico; La Mantia, Ignazio; Monti, Giulia; Ragusa, Martina; Macchi, Alberto (Frontiers in Allergy, 2025)
BackgroundChronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory condition characterized by persistent nasal obstruction, discharge, facial pressure, and olfactory dysfunction. CRSwNP significantly impairs quality of life (QoL), with olfactory loss being a particularly distressing symptom that affects food enjoyment, personal safety, and social interactions.MethodsThis study investigated the experiences of Italian patients with CRSwNP. A cross-sectional quantitative and qualitative survey (Google Forms questionnaire), collecting data on diagnosis, symptomatology, QoL impact, and treatment experiences was developed and distributed.ResultsThere were 155 respondents, with over half diagnosed with CRSwNP for more than a decade. Nasal obstruction was the primary symptom leading to medical consultation. Corticosteroid therapy and surgery showed limited and variable effectiveness in olfactory restoration. Biologic therapy, particularly dupilumab, demonstrated promising results, with approximately half of the patients reporting complete smell restoration.ConclusionsCRSwNP significantly affected patients' QoL, with olfactory dysfunction being a common and impactful symptom. While current treatments provide symptom relief, they do not always result in sustained olfactory improvement. Biologic therapy emerged as a promising option for olfactory restoration, underscoring the importance of personalized treatment strategies. Further research is warranted to explore the mechanisms of olfactory recovery and to optimize treatment protocols for CRSwNP.